Pengetahuan, Ketersediaan Fasilitas, Penyuluhan dan Petugas Kebersihan terhadap Perilaku Pemilahan Sampah Rumah Tangga : Knowledge, Availability of Facilities, Counseling and Cleaning Officers on Household Waste Segregation Behavior - Juniarti, Sri Wulan; Nina (Journal of Public Health Education, 2022)
Introduction: The problem of waste has become commonplace almost throughout the world including Indonesia. According to data from the National Waste Management Information System (SIPSN) in 2020, the most waste in Indonesia was contributed from household waste, 32.4%. Household waste is the largest distributor of waste in an area. Many people still haven't done waste sorting. Therefore, sorting household waste is very necessary because from the SIPSN results the most waste produced is household waste. Objective: This research aims to determine the relationship between knowledge, availability of facilities, counseling, and cleaning staff on household waste sorting behavior in the community of Cisalak Village, Sukmajaya District. Methods: This research is quantitative with a cross-sectional approach. The instrument in this research uses a questionnaire. The population in this study was all the people of Cisalak Village, Sukmajaya District, Depok City, totaling 2,760 respondents, the total sample was 366 respondents. The data used in this research is primary data obtained through observation and filling out questionnaires. Meanwhile, secondary data was obtained through documents from Cisalak Village, Sukmajaya District. Results: There is no relationship between knowledge (P = 0.266), availability of facilities (P = 0.074) and there is a relationship between counseling (P = 0.015) and cleaning staff (P = 0.001) on household waste sorting behavior. Conclusion: The knowledge and availability of facilities owned by the community in Cisalak Subdistrict is good so it has nothing to do with household waste sorting behavior. However, there are still some people who do not follow the counseling, making their knowledge about waste sorting still not good and some people think that cleaning staff do not sort waste, so there is a relationship between counseling and cleaning staff regarding household waste sorting behavior in Cisalak Village, Sukmajaya District.